Accuracy Code Cronic Obstructive Pulmonary Desease - Linda Widyaningrum; Astri Sri Wariyanti; Sauha Lulumanin; Lutfi Maratin (LPPM Universitas Duta Bangsa Surakarta, 2021)
Chronic Obstructive Pulmonary Disease is inflammation of the lungs that develops over a long period of time. This study determine the level of accuracy of the diagnosis code for Chronic Obstructive Pulmonary Disease. This research is a descriptive study, with a retrospective approach. Saturated samples were 100 cases of Chronic Obstructive Pulmonary Disease using nonprobability sampling technique. The research instruments were ICD-10, checklist, observation guide, interview guide, calculator and voice recorder. Data processing by editing, coding, data entry, tabulating, and presenting data. The analysis was carried out descriptively. The percentage of diagnosis code accuracy of Chronic Obstructive Pulmonary Disease is 60% and code inaccuracy is 40%. The code inaccuracy is 40 medical records of 100 documents. Factors that affect the accuracy of the diagnosis code are medical personnel (doctors), medical record officers as coders, and other health workers. The author suggests that more emphasis should be placed on doctors to clarify the writing of a diagnosis and use medical terminology for disease diagnosis in order to make it easier for coding officers to provide disease codes and affect the accuracy of patient disease codes, the officers should be more careful and careful during the disease coding process. So that there are no more medical record files that are not coded so that the resulting code is accurate, and coding officers should be more careful during the process of giving the diagnosis code so that there are no more inaccurate medical record files due to incorrect coding.